Assisting MSMEs in Implementing Digital Financial Applications (POS and E-Wallet) - Rani Nastakiah Fani; Muammar Rinaldi (International Journal of Applied Community Solutions, 2026)
Digital transformation has become an urgent need for Micro, Small, and Medium Enterprises (MSMEs) to increase competitiveness and operational efficiency. However, many MSMEs still face various obstacles in utilizing digital financial technology, particularly Point of Sales (POS) applications and e-wallet-based cashless payments. This community service program aims to provide intensive assistance to MSMEs in understanding, implementing, and maximizing the use of POS applications and digital payment systems. The implementation method consists of outreach, technical training, individual mentoring, and evaluation based on monitoring the progress of application usage. The program was carried out over two months and involved 20 MSMEs from the culinary, retail, and service sectors. The program results showed that 85% of participants successfully operated POS applications independently for recording daily transactions and managing inventory. Furthermore, 78% of MSMEs began accepting digital payments through e-wallets such as OVO, Dana, and GoPay, improving transaction efficiency and customer convenience. After the mentoring, there was an average 32% increase in financial recording accuracy and a 27% reduction in transaction times. Participants also demonstrated an increased understanding of financial digitalization, transaction security, and the benefits of automated report analysis from POS applications. Thus, this mentoring program has proven effective in improving digital financial literacy among MSMEs and is a strategic step in driving technology-based digital transformation. Follow-up programs are recommended to strengthen financial report management and integrate POS with digital marketing platforms.